FROM TRADITION TO INNOVATION: THE EVOLVING WOODEN HANDICRAFTS OF SAHARANPUR - Singhal, Aarooshi; Karuna (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Wood carving in Saharanpur is a heart of India’s cultural heritage. It is recognized for its glamorous designs and the craftsmanship of traditional artisans. This ancient art form connects the past with the present, offering a glimpse of India’s rich artistic history. It also sets the stage for future generations to continue this admired tradition. Recently, there has been a rise in modern adaptations that merge traditional aesthetics with contemporary influences. Artisans are now creating innovative designs that appeal today’s audience. Saharanpur’s wood-carving industry is transitioning from traditional Mughal and Kashmiri styles to modern practices, influences by changing global tastes and market demands. Wood carving art form has seen a significant shift in today’s society. Artists now blend this ancient craft with modern elements, creating wood art that appeals to innovative contemporary tastes. They use new techniques and viewpoints, making wood carving a reflection of our current culture and aesthetics. Artisans merge traditional skills with modern methods, producing pieces that honour their heritage while exploring new designs. These creations are not just functional but also express deep artistic sentiments. Exhibitions and galleries dedicated to this art have emerged, showcasing the range and creativity of wood art today. This on-going dialogue between tradition and modernity inspires both viewers and creators. It highlights the profound beauty and depth that wood carving can bring to our contemporary world.